Amino Acid Content in the Seeds of Vetch Varieties Under Saline Soil Conditions - U. T. Jumanov; T. X. Kuliyev; Sh. Payonov; J. DJaborov; M. Safarova (American Journal of Biodiversity, 2026)
This article presents data on the amino acid content in the seeds of vetch varieties Mirzacho‘l-1 (Vicia villosa Roth) and Mirzacho‘l-2 (Vicia sativa L.). The total amino acid content was 28.03 g/mg in the Mirzacho‘l-1 variety and 32.08 g/mg in the Mirzacho‘l-2 variety. Among the studied amino acids, the proportion of aspartate accounted for 36.62% in Mirzacho‘l-1 and 40.2% in Mirzacho‘l-2. The presence and activity of essential amino acids such as isoleucine, phenylalanine, and leucine contribute to the tolerance of vetch to saline conditions and low temperatures. It was determined that lysine is a limiting amino acid in vetch varieties. The Mirzacho‘l-1 variety is recommended for use as livestock feed and as a green manure (sideral) crop, while the Mirzacho‘l-2 variety is recommended for grain production under slightly saline soil conditions when sown in autumn and early spring.